PENDAMPINGAN PSIKOSOSIAL UNTUK PENGUATAN RESILIENSI KOMUNITAS TERDAMPAK BENCANA DI DESA SAPTA MARGA, KECAMATAN MANYAK PAYED, KABUPATEN ACEH TAMIANG, PROVINSI ACEH - Nahdah Fadhilah; Sari Rizky; Rahayu; Agresia Natalinsani Br Purba; Gunawan Sidabutar; Muhammad Habiburrahman (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
Flood disasters in Sapta Marga Village have significantly impacted the psychological condition of the community. This community service activity aims to strengthen community resilience through psychosocial assistance. The method used was a participatory approach involving sharing sessions for women, spiritual strengthening through Quran distribution and collective recitation, and psychosocial activities for children through coloring and educational games. The program was conducted on February 13–14, 2026. The results indicate reduced emotional burden, improved social interaction, and increased community motivation. The integration of psychosocial and spiritual approaches proved effective in post-disaster recovery.